Holistic Strategy in Building Competitive Advantage in the Digital Era and Market Disruption - Wahyu Sri Handono; Yulianto Umar Rofi’i; Upik Sri Sulistyawati (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2024)
This study aims to analyze the effect of a holistic strategy on a company's success in maintaining competitive advantage in the digital transformation era. The holistic strategy includes technology adoption, human resource development, business model innovation, customer orientation, and risk management. This study uses a quantitative approach with a survey method through a closed questionnaire distributed to managers and executives in 100 companies spread across various industrial sectors, including technology, manufacturing, services, and retail. Respondents were selected based on their company's involvement in digital transformation initiatives for at least two years. The collected data were analyzed using descriptive statistics and linear regression to evaluate the relationship between the independent (holistic strategy) and the dependent (competitive advantage) variables. The study results show that technology adoption, especially AI, big data, and IoT, significantly affects company performance and strengthens its competitive advantage. In addition, employee digital skills development, innovation in business models, and a focus on improving customer satisfaction have also been shown to play an important role in driving business growth. Effective risk management helps companies deal with market disruption and economic uncertainty to maintain their operations' sustainability. These findings emphasize the importance of integrating various elements in a holistic strategy to ensure a company's success in the era of dynamic digital competition. This research provides theoretical and practical contributions for business managers in formulating adaptive and sustainable strategies amidst technological disruption. The implications of these findings suggest that companies need to accelerate their digital transformation by strengthening the synergy between technology, human resources, innovation, and risk management to maintain their competitiveness in the global market.